Steering Handbook - Harrer, Manfred; Pfeffer, Peter; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This edited volume presents basic principles as well as advanced concepts of the computational modeling of steering systems. Moreover, the book includes the components and functionalities of modern steering system, which are presented comprehensively and in a practical way. The book is written by more than 15 leading experts from the automotive industry and its components suppliers. The target audience primarily comprises practicing engineers, developers, researchers as well as graduate students who want to specialize in this field.
Introduction and History -- Basic Principles of the Steering Process -- Steering -- Steering kinematics -- Basics of transverse dynamics -- Acoustics and vibrations -- Layout of steering systems -- Steering wheel -- Steering column and intermediate steering shaft -- Mechanical and hydraulic gears -- Tie rods -- Hydraulic power supply -- Electrically powered hydraulic steering -- Electric Power Steering systems -- Superimposed steering system -- All-wheel steering -- Steer-by-Wire -- Overview - driver assistance system -- Outlook - The future of steering.
Keywords: Automotive engineering; Multibody systems; Vibration; Mechanics, Applied; Mathematical models; Mechatronics; Automotive Engineering; Multibody Systems and Mechanical Vibrations; Mathematical Modeling and Industrial Mathematics; Mechatronics